STRATEGI MANAJEMEN KONFLIK DIMASA PANDEMI COVID-19 MAHASISWA KEPERAWATAN KOTA MAKASSAR - Kristan, Kristan; Hidayah, Nur; Farid Abidin, Muhammad (Jurnal Kesehatan, 2020)
Awareness in conflict management is very important for learners to consider. Students, as one of the largest numbers of people in educational institutions, have undoubtedly felt the effects of the Covid-19 crisis, where the learning environment, which is normally carried out face-to-face both on campus and in the field of practice, has turned online. Conflict is unavoidable, but it can be handled in such a way that it has a positive effect as a lesson. Growing knowledge of conflict management is one way of avoiding conflict. Conflict, depending on how the conflict is handled, can be negative (detrimental) but can be constructive (beneficial). The aim of this study was to identify the conflict management strategies of students of the nursing profession in the city of Makassar during the Covid-19 pandemic. The methodology in this study uses quantitative methods with a descriptive frequency distribution analysis style. The results of this research show that nursing students have a 100% conflict management strategy on a partnership strategy, then 94.6% on a compromise strategy, 93.9% on an avoidance strategy, 92.5% on an accommodation strategy, and 91.8% on a competition strategy. With the result that a collaborative conflict management approach is used by the prevailing conflict management strategy used by nursing career students in the town of Makassar. ABSTRAK Pengetahuan tentang manajemen konflik sangat penting untuk diketahui oleh mahasiswa. Mahasiswa sebagai salah satu individu yang jumlahnya paling banyak di institusi pendidikan tentunya sangat merasakan dampak pendemi Covid-19, dimana sistem pembelajaran yang biasanya dilakukan secara tatap muka baik di lingkungan kampus ataupun lahan praktek berubah menjadi daring. Konflik memang tidak bisa dihindari, melainkan dapat dikelola agar memberikan dampak positif sebagai sebuah pembelajaran. Salah satu cara mencegah terjadinya konflik ialah dengan meningkatkan pengetahuan manajemen konflik. Konflik dapat bersifat negatif (merugikan) tetapi dapat bersifat positif (menguntungkan), tergantung bagaimana konflik dikelola. Tujuan dalam penelitian ini adalah untuk mengetahui strategi manajemen konflik mahasiswa profesi ners pada masa pandemi covid-19 dikota Makassar. Metode pada penelitian ini menggunakan metode kuantitatif dengan desain Deskriptif Analisis Distribusi Frekuensi. Hasil pada penelitian ini menunjukan bahwa mahasiswa profesi ners memiliki strategi manajemen konflik 100% pada strategi kolaborasi, selanjutnya 94.6% pada strategi kompromi, 93.9% pada strategi menghindar, 92.5% pada strategi akomodasi dan 91.8% pada strategi kompetisi. Dengan kesimpulan bahwa strategi manajemen konflik yang dominan digunakan oleh mahasiswa profesi ners di kota makassar yaitu menggunakan strategi manajemen konflik kolaborasi.